High-Efficiency and High-Quality Photogalvanic Etching of the Silicon Doped N-Type Gallium Nitride Using Potassium Peroxomonosulfate Oxidant. (1st May 2022) - Guo, Sai; Zhang, Mingming; Qiao, Liqing; Hu, Huiqing; Shi, Kang
Abstract : Photogalvanic etching, or photo-assisted electroless etching, is a simple wet-etching approach to fabricate n-type gallium nitride (GaN)-based devices without any external power supply. However, the current technology is far from practical because efficient etching can only be realized by a potassium persulfate (PS) oxidant/alkaline electrolyte system that inevitably bends the etching surface. In this study, we proposed and tested a new potassium peroxomonosulfate (PMS) oxidant/weak acid electrolyte system for the photogalvanic etching of platinum (Pt) photo-mask patterned GaN wafers. A novel finding is that Pt can catalyze PMS decomposition in acids, predominantly generating singlet oxygen ( 1 O2 ), whose onset reduction potential is 0.95 V higher than PS. Under 25.4 mW.cm 2 ultraviolet (UV) irradiation, PS-driven photogalvanic etching of inert silicon-doped GaN (si-GaN) wafers is invalid, whereas the new system enables high efficiency and quality etching in 20 mM PMS + 0.1 M K2 SO4 electrolyte (pH = 3.0). The etching rate reaches 12.0 nm.min −1, while the as-prepared groove bottoms have nanometer surface flatness, and the surface roughness (Ra) attains 5.25 nm (5 × 5 μ m 2 ). In summary, the PMS/weak acid electrolyte system makes photogalvanic etching is a promising practical technique.